2017
DOI: 10.3758/s13414-017-1353-2
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble coding remains accurate under object and spatial visual working memory load

Abstract: A number of studies have provided evidence that the visual system statistically summarizes large amounts of information that would exceed the limitations of attention and working memory (ensemble coding). However the necessity of working memory resources for ensemble coding has not yet been tested directly. In the current study, we used a dual task design to test the effect of object and spatial visual working memory load on size averaging accuracy. In Experiment 1, we tested participants' accuracy in comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…We further extended the previous evidence by showing that centroid extraction is also not costly when there is variance in the size of the elements and when attention is split between the centroid and the less precise item locations. Our findings are consistent with recent research suggesting that working memory load has no bearing on ensemble coding (Epstein & Emmanouil, 2017; but see also Bauer, 2017). Taking these results together with those from Experiment 2, we can conclude that the centroid is a simple summary that can be represented upon very brief views and also along with another spatial summary.…”
Section: Resultssupporting
confidence: 93%
“…We further extended the previous evidence by showing that centroid extraction is also not costly when there is variance in the size of the elements and when attention is split between the centroid and the less precise item locations. Our findings are consistent with recent research suggesting that working memory load has no bearing on ensemble coding (Epstein & Emmanouil, 2017; but see also Bauer, 2017). Taking these results together with those from Experiment 2, we can conclude that the centroid is a simple summary that can be represented upon very brief views and also along with another spatial summary.…”
Section: Resultssupporting
confidence: 93%
“…Chong & Treisman, 2003;Corbett, Wurnitsch, Schwartz, & Whitney, 2012;Epstein & Emmanouil, 2017). Many of these studies assume that multiple subsets can be (almost) perfectly segmented based on the color or spatial cues prior to ensemble extraction.…”
Section: Experiments 2 Categorization In the Domain Of Size And Ensembmentioning
confidence: 99%
“…Instead, Utochkin and Tiurina (2014) found that heterogeneity does not affect accuracy, suggesting that all items are computed over. Ensemble perception also works even when subjects are under working memory load (Epstein & Emmanouil 2017). These results suggest that large numbers of items are explicitly represented in early stages of visual perception prior to storage in VWM.…”
Section: The Challenge From Flexible Resourcesmentioning
confidence: 99%